Does Public Service Broadcasting Serve the Public? The Future of Television in the Changing Media Landscape - M. van Dijk; Richard Nahuis; D. Waagmeester (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2005)
The media landscape is subject to substantial technological change. In this Discussion Paper we analyse how technological trends affect the economic rationale for PSB. After identifying the aims and nature of PSB, we derive eight possible market failures from the specific economic characteristics of information. The changing relevance of these market failures is subsequently discussed in the light of the technological changes. Based on this analysis, we argue that public service broadcasting (PSB) for the digital age should be light in the sense that it has a much smaller mandate. The main reason for this conclusion is that, due to technological developments, many market failures in the broadcasting industry are no longer relevant. The broadcasting market thus functions more and more like a normal market. This implies that the allocation tends to the efficient outcome, as long as consumer valuation is properly accounted for. This is not the case when there are externalities and possibly not when it comes to valuing quality. In the presence of these market failures, an efficient allocation is not warranted in the broadcasting industry. It is these remaining market failures that give a future PSB a right to exist.
Keywords: 330